Phylogeny and mycotoxin profiles of pathogenic Alternaria and Curvularia species isolated from date palm in southern Tunisia - Rabaaoui, Amal; Masiello, Mario; Somma, Stefania; Crudo, Francesco; Dall’Asta, Chiara; Righetti, Laura; Susca, Antonia; Logrieco, Antonio Francesco; Namsi, Ahmed; Gdoura, Radhouane; Werbrouck, Stefaan P. O.; Moretti, Antonio (Frontiers in Microbiology, 2022)
Date palm (Phoenix dactylifera L.), is a widely cultivated crop across North Africa, with about 300 thousand tons of fruits produced per year, in Tunisia. A wide range of fungal pathogens has been associated with leaf spots of date palm, Alternaria species being the most frequently reported. Symptomatic leaves of Deglet Nour variety were randomly collected in six localities in Tunisia. We used a polyphasic approach to identify 45 Alternaria and five Curvularia strains isolated from date palm, confirming their pathogenicity. Sequencing of allergen Alt-a1, glyceraldehyde-3-phosphate dehydrogenase (gpd) and calmodulin genes allowed us to group 35 strains in Alternaria Section, and 10 strains in Ulocladioides section. Based on sequencing analyses of Internal Transcribed Spacer, gpd and elongation factor genomic regions, all Curvularia strains were identified as Curvularia spicifera. All Alternaria and Curvularia species tested on date palm plantlets proved to be pathogenic, fulfilling Koch’s postulates. Although no significant differences were observed among the species, the highest mean disease severity index was observed in A. arborescens, while the lowest corresponded to C. spicifera. The capability of these strains to produce mycotoxins in vitro was evaluated. None of the A. consortialis strains produced any known Alternaria mycotoxin, whereas more than 80% of the strains included in Alternaria section Alternaria produced variable amounts of multiple mycotoxins such as alternariol, alternariol monomethyl ether, altenuene, tenuazonic acid and tentoxin. Curvularia spicifera strains produced detectable traces of fumonisins B. This work reports a first comprehensive multidisciplinary study of mycotoxigenic Alternaria species and C. spicifera associated with leaf spot disease on date palm.